Analisis Postur Kerja Mengurangi Musculoskeletal Disorders Menggunakan Metode RULA dan REBA Pada Bengkel Aryka Motor - Muhammad Ilham Adelino; Tomy Andra Salputra; Nidya Try Arnika; Hermanto Hermanto; Yogi Yusrila (Publikasi Indonesia, 2023)
Aryka Motor Workshop is a small micro business in the form of a motorcycle repair shop located on Jln. Cross Sumatra-Pematang Panjang, Sijunjung Regency. At Aryka Motor Workshop, there are several employees whose posture is not ergonomic at work. This study aims to determine the level of work risk experienced by employees at Aryka Motor due to work posture and find solutions to improve this work posture. This study used the Rapid Upper Limb Assessment (RULA) method to assess work posture or worker activity in the upper limb when doing work. This study analyzes and evaluates the body posture of one of the employees in the machine disassembly and installation operator. The results of the study show that two employees have a work posture with a high level of risk. In this regard, it is necessary to carry out an investigation and a change in work posture needs to be carried out immediately by providing a work desk.